2018
DOI: 10.1159/000488474
|View full text |Cite|
|
Sign up to set email alerts
|

LncRNA-AK131850 Sponges MiR-93-5p in Newborn and Mature Osteoclasts to Enhance the Secretion of Vascular Endothelial Growth Factor a Promoting Vasculogenesis of Endothelial Progenitor Cells

Abstract: Background/Aims: In the process of bone development and remodeling, the vasculature is regarded as the communicative network between the bone and neighboring tissues. Recently, it has been reported that the processes of angiogenesis and osteogenesis are coupled temporally and spatially. However, few studies reported the relationship and relevant mechanism between osteoclastogenesis and vasculogenesis. Methods: Arraystar Mouse lncRNA microarray V3.0 was firstly used to analyze the differentially expressed lncRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 55 publications
0
21
0
Order By: Relevance
“…Thus, lncRNA-Jak3 may be a potential target candidate for MSU-induced osteoclast activation, and its role in physiological osteoclast differentiation should also be further investigated. Recently, lncRNA AK131850 was also described to be involved in the different stages of osteoclastogenesis 113 . Surprisingly, this lncRNA is a natural antisense transcript of VEGF and it can modulate endothelial progenitor cells 113 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, lncRNA-Jak3 may be a potential target candidate for MSU-induced osteoclast activation, and its role in physiological osteoclast differentiation should also be further investigated. Recently, lncRNA AK131850 was also described to be involved in the different stages of osteoclastogenesis 113 . Surprisingly, this lncRNA is a natural antisense transcript of VEGF and it can modulate endothelial progenitor cells 113 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, lncRNA AK131850 was also described to be involved in the different stages of osteoclastogenesis 113 . Surprisingly, this lncRNA is a natural antisense transcript of VEGF and it can modulate endothelial progenitor cells 113 . AK131850 acts as an endogenous sponge for miR-93-5p, which alleviates the repression on VEGF expression and, consequently, promotes proliferation, differentiation, migration, and tube formation of endothelial progenitor cells 113 .…”
Section: Introductionmentioning
confidence: 99%
“…Most studies regarding the relationship between lncRNA and miRNA concentrated on the effects on osteogenic differentiation, and there have been few related studies on osteoclasts. One study showed that, during osteoclastogenesis, lncRNA-AK131850 can act as a sponge for miR-93-5p in newborn and mature osteoclasts, increasing vascular endothelial growth factor A (VEGF-A) transcription, expression, and secretion by reducing miR-93-5, thereby promoting vasculogenesis of endothelial progenitor cells [109]. Although this finding was not directly related to osteoporosis, it was closely related to osteoclasts, so it may be useful in developing treatments for osteoporosis.…”
Section: Interactions Between Lncrnas and Mirnasmentioning
confidence: 99%
“…Endothelial progenitor cells (EPCs) are precursor cells of vascular endothelial cells, which have the ability to proliferate, migrate, and differentiate into cells arranged along the lumen of blood vessels [14]. It has been found in previous studies that EPCs can enhance the osteogenic activity of pre-osteoblasts [15] and play an important role in bone formation and repair [16,17]. Adipose-derived mesenchymal stem cells (ASCs) are extracted from adipose tissue with high proliferative capability and multi-differential potential [18,19].…”
Section: Introductionmentioning
confidence: 99%